Resonance control system of a vortex wind turbine for energy generation through structural redesign - Yauri Rodríguez, Ricardo (2023)
The consumption of electrical energy is increasing due to problems related to the deficient energy supply in certain localities, which affects the basic needs in rural communities where, currently, the efforts to distribute electricity by the authorities, through common technologies, are not enough. On the other hand, there is also the problem of the overexploitation of non-renewable energies, which produce large amounts of C02. To reduce these problems, renewable energies that do not generate polluting waste are used, but the ability of engineers is needed to achieve prototypes that give good results. The purpose of this research is to carry out the design and simulation of a control system and redesign of a Vortex wind turbine mast to keep it in resonance and generate electrical energy. The study objectives are met by verifying the specific results through requirements analysis, simulation design, and system validation. As a result, the parameters to generate vortices and keep the system in resonance were identified. In addition, the redesign of the mast of the Vortex wind turbine was obtained.